Matrix metalloproteinases and metastasis - Kleiner, David E.; Stetler-Stevenson, William G. (Cancer chemotherapy and pharmacology, 1999)
Metastatic disease is responsible for the majority of cancer-related deaths, either directly due to tumor involvement of critical organs or indirectly due to complications of therapy to control tumor growth and spread. An understanding of the mechanisms of tumor cell invasion and metastasis may be important for devising therapies aimed at preventing tumor cell spread. Matrix metalloproteinases (MMPs) are a family of zinc-dependent endoproteinases whose enzymatic activity is directed against components of the extracellular matrix (ECM). In humans, 16 members of this family have been identified by cloning and sequencing. These proteinases are linked by a core of common domain structures and by their relationship to a family of proteinase inhibitors called the tissue inhibitors of metalloproteinases (TIMPs). Four members of the TIMP family have been cloned and sequenced in humans and they inhibit MMPs by forming tight-binding, noncovalent associations with the active site of the MMPs. MMPs facilitate tumor cell invasion and metastasis by at least three distinct mechanisms. First, proteinase action removes physical barriers to invasion through degradation of ECM macromolecules such as collagens, laminins, and proteoglycans. This has been demonstrated in vitro through the use of chemoinvasion assays and in vivo by the presence of active MMPs at the invasive front of tumors. Second, MMPs have the ability to modulate cell adhesion. For cells to move through the ECM, they must be able to form new cell-matrix and cell-cell attachments and break existing ones. Using a cell transfection system that altered the ratio of MMP-2 to TIMP-2 we have demonstrated significant variation in the adhesive phenotype of tumor cells. Finally, MMPs may act on ECM components or other proteins to uncover hidden biologic activities. For example, the angiogenesis inhibitor angiostatin may be produced from plasminogen by MMP action and laminin-5 is specifically degraded by MMP-2 to produce a soluble chemotactic fragment. Thus MMPs play multiple key roles in facilitating the metastasis of tumor cells. Therapies designed to interfere with specific MMP actions may be useful in the control of metastatic disease.